South Africa : Macro Policy Mix and Its Effects on Growth and the Real Exchange Rate--Empirical Evidence and GIMF Simulations - Canales Kriljenko, Jorge (Departmental Papers; Departmental Paper ;, 2011)
This paper examines whether a mix of tighter fiscal policy, looser monetary policy, and greater reserve build-up would increase growth and depreciate the rand in real terms. The experience of South Africa over the last twenty years is looked at using a number of econometric techniques that control for the external environment.